Teofani sebagai Respon terhadap Krisis Korupsi di Indonesia: Analisis Sosio-Retoris Mazmur 18:8-16 - Simanjuntak, Markus Adelbert (Sekolah Tinggi Teologi Berita Hidup, 2025)
This study explores the concept of theophany in Psalm 18:8-16 as a theological framework for critiquing and responding to the systemic corruption crisis in Indonesia. Employing a socio-rhetorical approach that integrates inner texture analysis, ideological criticism, and empirical data on corruption from 2014-2025, this research explores how theophany narratives can inspire moral resistance against corrupt practices. Findings suggest that theophany, as a manifestation of divine power, offers a robust theological basis for systemic reform, prophetic critique of elites, and affirmation of justice that transcends human law. This research introduces the concept of